Inovasi dan Strategi Pemasaran Digital untuk Keberlanjutan UMKM Kerak Telor Tradisional - Andi Suhandi; Azmi Muhammad Habibie; Sri Wahyuningsih; Ari Mulyono Hadi; MH Ainulyaqin (JPPI: Jurnal Pengabdian Pelita Insani, 2026)
Community service activities were conducted at the Kerak Telor Juara Yudi (Yudi Egg Cracker) MSME, located at Wibawa Mukti Stadium, Cikarang, Bekasi Regency. This MSME faced several challenges, such as declining customer interest, lack of funding, ineffective digital marketing, poor financial management, and operational difficulties due to weather. These issues resulted in declining sales and hindered business growth. The goal of this activity was to improve the competitiveness and capabilities of the MSME through assistance with digital marketing, product and packaging innovation, and simple financial management training. This activity took place in three stages: preparation, implementation, and evaluation. The results demonstrated an increased understanding of branding, social media promotion, product innovation, and financial management among entrepreneurs. The implementation of the strategies successfully expanded the market and increased revenue, despite funding limitations.